Solid dispersion of itraconazole in corn starch (physical mixture) against different media: wettability and surface thermodynamics - Jamil, Azwa (2017)
ltraconazole is an antifungal drug and categorize as Biopharmaceutical Classifiction System (BCS) Class II which has good permeability but poor solubility. The purpose of this research project was to determine the enhancement of itraconazole solubility in the presence of com starch against different media in terms of surface thermodynamics. Surface thermodynamics includes contact angle, surface energy, and work of adhesion. The samples were prepared in itraconazole:com starch ratio which were 90: 10, 80:20, 70:30, 60:40 and 50:50 using physical mixture. Media used for this project was simulated gastric fluid (SGF) and simulated intestinal fluid (SIF) to mimic the condition inside the gastric and intestinal part of the body. Sessile drop method was used to calculate the contact angle using static contact angle instrument with OCA15 software. The results showed the contribution of com starch in the improvement of the wettability and the rate of wetting of the drug. The lower in contact angle resulted in increased the surface energy and work of adhesion. The best samples preparation was 50:50 that represented the optimum wetting performance. As conclusion, the presence of com starch improved the wetting phenomenon in comparison with itraconazole alone.